Edukacja medialna: ziemia wciaz nieznana?… - Ogonowska, Agnieszka (Kultura-Społeczeństwo-Edukacja, 2012)
The paper describes the nature of media education, its main domains and aims of education in this matter, the state of research and practical solutions in Poland and the world as well as the diffi culties related to the student and shaping the media competences.